2016
DOI: 10.1007/s11356-016-7519-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dicyandiamide and acetylene on N2O emissions and ammonia oxidizers in a fluvo-aquic soil applied with urea

Abstract: Ammonia-oxidizing bacteria (AOB) and ammonia-oxidizing archaea (AOA) are crucial for N 2 O emission as they carry out the key step of nitrification. Dicyandiamide (DCD) and acetylene (C 2 H 2 ) are typical nitrification inhibitors (NIs), while the comparative effects of these NIs on N 2 O production and ammonia oxidizers' (AOB and AOA) growth are unclear. Four treatments including a control, urea, urea + DCD, and urea + C 2 H 2 were set up to investigate their effect of inhibiting soil nitrification, nitrifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 63 publications
3
3
0
Order By: Relevance
“…The AOA phylogenetic analysis suggested that the AOA gene sequences were aligned to group 1.1b and group 1.1a, whereas the T-RF 540 bp belonging to the group 1.1a showed the highest relative abundance. These results were in well agreement with former studies that group 1.1a could possibly be more abundant in acidic red soils, while group 1.1b was more adaptable to neutral and alkaline soils [21,46]. Former results also suggested that the group 1.1a-associated lineage could possibly be tolerant with limiting oxygen than soil group 1.1b [18].…”
Section: Community Compositions Of Ammonia Oxidizerssupporting
confidence: 92%
See 2 more Smart Citations
“…The AOA phylogenetic analysis suggested that the AOA gene sequences were aligned to group 1.1b and group 1.1a, whereas the T-RF 540 bp belonging to the group 1.1a showed the highest relative abundance. These results were in well agreement with former studies that group 1.1a could possibly be more abundant in acidic red soils, while group 1.1b was more adaptable to neutral and alkaline soils [21,46]. Former results also suggested that the group 1.1a-associated lineage could possibly be tolerant with limiting oxygen than soil group 1.1b [18].…”
Section: Community Compositions Of Ammonia Oxidizerssupporting
confidence: 92%
“…The AOB phylogenetic analyses showed that Nitrosospira cluster like AOB exclusively predominate the community compositions of bacterial ammonia-oxidizers in acidic red soils, which were in line with results obtained from former agriculture soils [37,46]. It was proposed that AOB belonged to Nitrosomonas spp (cluster 7&8) were exclusively detected in the rice paddies, whereas AOB within Nitrosospira spp (cluster 2&0) was observed only in the upland soils [37,46]. However, no such distinct phenomenon was observed in our study, which might relate to the soil samplings used for the physiological analysis (day in the drainage period).…”
Section: Community Compositions Of Ammonia Oxidizerssupporting
confidence: 87%
See 1 more Smart Citation
“…The 50 μl reaction mixture contained 25 μl Premix Ex Taq (TaKaRa, Dalian, China), 1 μl of each primer (10 μM) and 2 μl of diluted template DNA (1–10 ng). The labelled PCR products were purified using the Gel Extraction Kit (Qiagen, Hilden, Germany), and then, the purified PCR products were digested with restriction enzymes HpyCH4V for AOA amoA gene (Hu et al ., ), RsaI for AOB amoA gene (Wang et al ., ), HaeIII for nirK gene (Guo et al ., ), MspI for nirS gene (Guo et al ., ) and MspI for nosZ gene (Hu et al ., ) respectively. The size and relative abundance of T‐RFs were determined by a 3730xl DNA Analyser (Applied Biosystems, Carlsbad, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Bronson et al studied the decomposition rate and nitrification inhibition of DCD . As a nitrification inhibitor, DCD has an impact on N 2 O emissions. DCD is an important industrial raw material, which has many applications, not only in the printing and dyeing industry but also in the electronics industry. In addition, DCD is also used as an intermediate in fine chemicals. In medicine, DCD is used to produce guanidine nitrate and sulfa drugs.…”
Section: Introductionmentioning
confidence: 99%